The Impact Of The Internet Of Things On The Creative Accounting Practice: Using Big Data - Abdul Razzak Alshehadeh; Murad Ali Ahmad Al-Zaqeba; Mohammad Sulieman Jaradat; Haneen A. Alkhawaja; Habes Hatamleh (growing science, 2024)
Non-Indexed Publication